Development of Blended Learning-Based Science Module on Sound Material to Improve Learning Outcomes of Fourth-grade Elementary School Students - Pramyta Nur Insani; Su'ad Su'ad; Ahmad Hariyadi (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research is motivated by the lack of learning resources that can support learning during the learning process, both face-to-face and independently, which causes a decline in student learning outcomes. This study aims to design and analyzing the effectiveness of blended learning-based science learning modules on sound material to improve learning outcomes of fourth-grade elementary school students. This study is a research and development (R D) by Borg and Gall, with an operational test design using a pretest-posttest control group design. There are 33 students in an experimental class and 31 students in a control class in grade IV. The results showed the module is valid and effective with good criteria, for the experimental class with pretest results of 53.5 and posttest of 71.5 with n-gain of 0.47 medium criteria. Meanwhile, in the control class, pretest results were obtained of 53.1 and posttest of 61.8 with n gains of 0.19 low criteria. Compared to the control group, the experimental group saw a greater improvement in learning outcomes in the test of the materials' efficacy. The blended learning module created for this research can be used as a resource for both students and educators to help them reach their educational goals.